A Study of Human Leukocyte Antigen Mismatched Cellular Therapy (Stem Cell Microtransplantation) in High‐Risk Myelodysplastic Syndrome or Transformed Acute Myelogenous Leukemia. (2nd February 2016) - Hu, Kai-Xun; Sun, Qi-Yun; Guo, Mei; Qiao, Jun-Xiao; Yu, Chang-Lin; Qiao, Jian-Hui; Dong, Zheng; Sun, Wan-Jun; Zuo, Hong-Li; Huang, Ya-Jing; Cai, Bo; Ai, Hui-Sheng
Abstract : The effects and toxicity of combination human leukocyte antigen‐mismatched hematopoietic stem cell microtransplantation and chemotherapy were evaluated in patients with myelodysplastic syndrome (MDS) and transformed acute myelogenous leukemia (tAML). Patients with MDS had significantly higher overall response and complete response rates and higher 24‐month overall survival than those with tAML. No graft‐versus‐host disease was observed in the cohort. Abstract : The treatment outcomes of myelodysplastic syndrome (MDS) and transformed acute myelogenous leukemia (tAML) remain very unsatisfactory. We designed a combination of human leukocyte antigen (HLA)‐mismatched hematopoietic stem cell microtransplantation (MST) with chemotherapy for patients with MDS and tAML and evaluated its effects and toxicity. Patients were between 13 and 79 years old. Patients with MDS ( n = 21) were given HLA‐mismatched MST combined with decitabine and cytarabine; patients with tAML ( n = 22) were given HLA‐mismatched MST combined with decitabine and cytarabine, and also mitoxantrone. Patients in complete remission (CR) also received MST plus decitabine and medium‐dose cytarabine chemotherapy without graft‐versus‐host disease (GVHD) prophylaxis. The overall response rate of the patients with MDS was significantly higher than that of those with tAML (81% vs. 50%; p = .03). The CR rates were 52.4% and 36.4% in the two groups, respectively. There was no difference in the cytogenetic CR rate between the MDS and tAML groups (85.7% vs. 70%, respectively; p = .7). The 24‐month overall survival of the patients with MDS was significantly higher than that of the patients with tAML (84.7% and 34.1%, respectively; p = .003). The median recovery times of neutrophils and platelets were, respectively, 14 and 17 days in the patients with MDS, and 16 and 19 days in those with tAML. The treatment‐related mortality rates were 4.8% and 18.2%, respectively, in the MDS and tAML groups ( p = .34). No GVHD was observed in any patient. Microtransplantation combined with decitabine and chemotherapy may provide a novel, effective, and safe treatment for high‐risk MDS and tAML. Significance: Microtransplantation (MST) refers to regular chemotherapy combined with granulocyte colony‐stimulating factor‐mobilized peripheral blood stem cell infusion of human leukocyte antigen‐mismatched donor cells without using immunosuppressive agents. It aims to support hematopoietic recovery and perform graft‐versus‐leukemia (GVL) effects but differs from traditional allogeneic stem cell transplantation because the rate of donor cell chimerism is low and there is and no graft‐versus‐host disease (GVHD) risk. Thus, a trial was designed to evaluate the safety and efficacy of MST in patients with myelodysplastic syndrome and those with transformed acute myelogenous leukemia. Higher complete remission and cytogenetic complete response rates were observed, and the treatment improved disease progress‐free survival, sped hematopoietic recovery, and avoided GVHD.